Decoding Spatial Memory Retrieval in Cubical Space Using fMRI Signals - Guo, Jiahe; Zhang, Kai; Zhang, Jianyu; Zhao, Rui; Liang, Yibo; Lin, Yu; Yu, Shengping; Qin, Wen; Yang, Xuejun (Frontiers in Neural Circuits, 2021)
The way spatial memory retrieval is represented in the brain remains unclear to date. Previous studies have displayed a hippocampus-centred navigation network using functional magnetic resonance imaging (fMRI) analysis. There have been some studies on the representation of navigation behaviour by signal distribution patterns, but only in the hippocampus and adjacent structures. In this study, we aimed to determine (1) the brain regions that represent information in both intensity and distribution patterns during spatial memory retrieval and (2) whether the patterns of neural responses represent spatial memory retrieval behaviour performance. Both univariate (GLM) and multivariate pattern analysis (MVPA) were employed to reveal the spatial distributions of brain responses elicited by spatial memory retrieval. Correlation analyses were performed to detect the correspondences between brain responses and behaviour performance. We found that spatial memory retrieval occurred in widespread brain regions, including the bilateral hippocampi, bilateral superior frontal gyrus, bilateral superior parietal lobules, bilateral occipital lobes, and cerebellum. The amplitude of activation in the left hippocampus showed a significantly negative correlation (r=-0.46, p=0.039) with the number of task completions. Additionally, within-subject classification accuracies based on the BOLD signal patterns of rMTG rostral areas in the Brainnetome Atlas showed a significant positive correlation (r=0.78, p<0.0001) with retrieval accuracy. In summary, our findings have implications for understanding the separation between navigational and nonnavigational states and emphasizing the utility of MVPA in the whole brain.